2018
DOI: 10.1016/j.foodchem.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Psidium cattleianum fruits: A review on its composition and bioactivity

Abstract: Psidium cattleianum Sabine, commonly known as araçá, is a Brazilian native fruit, which is very juicy, with sweet to sub acid pulp and a spicy touch. The fruit can be eaten fresh or processed into juice, jellies and ice creams. Araçás are source of vitamin C, minerals, fatty acids, polysaccharides, volatile compounds, carotenoids and phenolic compounds, which can provide nutrients and phytochemical agents with different biological functions. Different pharmacological studies demonstrate that P. cattleianum exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 63 publications
(100 reference statements)
2
28
0
2
Order By: Relevance
“…Selections of 'Arazá' species were grouped into 'Arazá Amarillo' (AA -P. cattleyanum f. lucidum) and 'Arazá Rojo' (AR -P. cattleyanum f. cattleyanum) in accordance with the botanical forms and differences in their skin color. Differences found for this fruit were also related to the results of fruit weight, pH, titratable acidity (TA) and total soluble solids (SS), being comparable with previous studies (Medina, et al, 2011;dos Santos Pereira, et al, 2018). 'Guayabo del país' (GO) were larger in size and displayed greater fresh mass than the other fruits.…”
Section: Physicochemical Characterizationsupporting
confidence: 88%
See 2 more Smart Citations
“…Selections of 'Arazá' species were grouped into 'Arazá Amarillo' (AA -P. cattleyanum f. lucidum) and 'Arazá Rojo' (AR -P. cattleyanum f. cattleyanum) in accordance with the botanical forms and differences in their skin color. Differences found for this fruit were also related to the results of fruit weight, pH, titratable acidity (TA) and total soluble solids (SS), being comparable with previous studies (Medina, et al, 2011;dos Santos Pereira, et al, 2018). 'Guayabo del país' (GO) were larger in size and displayed greater fresh mass than the other fruits.…”
Section: Physicochemical Characterizationsupporting
confidence: 88%
“…Most of the studies used the whole fruit, but some of them (Medina, et al, 2011) evaluated the composition on the fruit flesh. For the method of extraction, some authors use a multi-step extraction procedure including long periods of maceration with solvents with different polarities and removal of fat soluble substances prior phenolic contents analysis, while others use more simple methods (dos Santos Pereira, et al, 2018). When compared with local results found for these native fruits, we obtained relative higher ascorbic acid content and lower total polyphenol content (Feippe, et al, 2011;Silveira, et al, 2016).…”
Section: Bioactive Compoundsmentioning
confidence: 67%
See 1 more Smart Citation
“…O araçá vermelho (Psidium cattleianum Sabine) é um fruto silvestre pertencente à família das Myrtaceae, proveniente da Mata Atlântica brasileira. Normalmente é colhido da vegetação nativa ou de pequenos pomares domésticos e comercializado apenas ocasionalmente, sendo ainda pouco conhecido (DOS SANTOS PEREIRA et al, 2018;LIMA et al, 2019). No entanto, o araçá apresenta elevado potencial econômico devido a sua composição físico-química e propriedades bioativas relacionadas, na sua maioria, aos compostos fenólicos e ácido ascórbico, que apresentam uma alta capacidade antioxidante (MCCOOK-RUSSELL et al, 2012).…”
Section: Introductionunclassified
“…It has been reported that its extract reduces metastasis of lung cancer [ 4 ]. It possesses anticancer [ 5 7 ], antioxidant, antimicrobial, anti-inflammatory, and antidiabetic activity [ 2 , 8 ]. Anticancer activity is due to presence of beta caryophyllene [ 9 ].…”
Section: Introductionmentioning
confidence: 99%